Selective intraarterial hypothermia combined with mechanical thrombectomy for acute cerebral infarction based on microcatheter technology: A single-center, randomized, single-blind controlled study - Yue Wan; Yue Wan; Hao Tian; Hui Wang; DaPeng Wang; HaiWei Jiang; Qi Fang (Frontiers in Neurology)
ObjectiveTo investigate the safety and efficacy of selective intraarterial hypothermia combined with mechanical thrombectomy in the treatment of acute cerebral infarction based on microcatheter technology.MethodsA total of 142 patients with anterior circulation large vessel occlusion were randomly assigned to the hypothermic treatment group (test group) and the conventional treatment group (control group). National Institutes of Health Stroke Scale (NIHSS) scores, postoperative infarct volume, the 90-day good prognosis rate (modified Rankin Scale (mRS) score ≤ 2 points), and the mortality rate of the two groups were compared and analyzed. Blood specimens were collected from patients before and after treatment. Serum levels of superoxide dismutase (SOD), malondialdehyde (MDA), interleukin-6 (IL-6), IL-10, and RNA-binding motif protein 3 (RBM3) were measured.ResultsThe 7-day postoperative cerebral infarct volume [(63.7 ± 22.1) ml vs. (88.5 ± 20.8) ml] and NIHSS scores at postoperative Days 1, 7, and 14 [(6.8 ± 3.8) points vs. (8.2 ± 3.5) points; (2.6 ± 1.6) points vs. (4.0 ± 1.8) points; (2.0 ± 1.2) points vs. (3.5 ± 2.1) points] in the test group were significantly lower than those in the control group. The good prognosis rate at 90 days postoperatively (54.9 vs. 35.2%, P = 0.018) was significantly higher in the test group than in the control group. The 90-day mortality rate was not statistically significant (7.0 vs. 8.5%, P = 0.754). Immediately after surgery and 1 day after surgery, SOD, IL-10, and RBM3 levels in the test group were relatively higher than those in the control group, and the differences were statistically significant. Immediately after surgery and 1 day after surgery, MDA and IL-6 levels in the test group were relatively reduced compared with those in the control group, and the differences were statistically significant (P < 0.05). In the test group, RBM3 was positively correlated with SOD and IL-10.ConclusionMechanical thrombectomy combined with intraarterial cold saline perfusion is a safe and effective measure for the treatment of acute cerebral infarction. Postoperative NIHSS scores and infarct volumes were significantly improved with this strategy compared with simple mechanical thrombectomy, and the 90-day good prognosis rate was improved. The mechanism by which this treatment exerts its cerebral protective effect may be by inhibiting the transformation of the ischaemic penumbra of the infarct core area, scavenging some oxygen free radicals, reducing inflammatory injury to cells after acute infarction and ischaemia–reperfusion, and promoting RBM3 production in cells.